APLIKASI PERPUSTAKAAN PADA SMA N1 KELUMBAYAN BARAT MENGGUNAKAN VISUAL BASIC - Rita Irviani; Rossi Oktaviana (LPPM STMIK Pringsewu, 2017)
The purpose of making the library application was to simplify the data seaching process and make the librarian easier such as borrow and return books and to know the late of returning books at the library. Model of Visual Basic (VB) was used in the development of this system. There were some necessary data in making the application such as members,books, borrowers, returning, rack book, and category book. From the data it was expected could be the basis to present the important informasion quicly and accurately. Because the system in saving and manage the data were changed from manual become computerized it was expedted to make the librarian prosess more effective.